(untitled) (Revista Contexto & Saúde, 2022)
Considering health education as a fundamental component in the care process in the pandemic scenario, this research aimed to identify the educational actions that were proposed in the context of primary health care. To this end, an analysis of the documents produced by the Health Departments of the states and the Federal District was carried out. In general, these documents presented guidelines on how to conduct educational activities remotely using various technological mechanisms. The most frequently cited contents corresponded to those aimed at preventing and controlling COVID-19 in the community. The educational materials were listed as strategic instruments in the dissemination of information and in the fight against fake news. This study contributes to the understanding of health education in primary care in the complex pandemic scenario of COVID-19.